The effect of coniferaldehyde on neurite outgrowth in neuroblastoma Neuro2a cells. (December 2019) - Jeon, Jieun; Kwon, Huiyoung; Cho, Eunbi; Kim, Kyung Sook; Yun, Jeanho; Lee, Young Choon; Kim, Dong Hyun
Abstract: Neurite outgrowth is the differentiation process by which neurons establish synapses. In the dentate gyrus of the hippocampus, new neurons are constantly produced and undergo neurite outgrowth to form synapses, and this process is involved in cognitive ability. Therefore, if an agent could modulate neurite outgrowth, it could potentially be developed as a compound for modulating cognitive ability. In this study, we examined whether coniferaldehyde, a natural compound, regulates neurite outgrowth in Neuro2a cells. We ascertained morphological changes and measured the percentage of neurite-bearing cells and neurite lengths. Coniferaldehyde significantly increased the percentage of neurite-bearing cells, and the length of neurites in a concentration-dependent manner, without inducing cell death. We then have identified that, coniferaldehyde activates the extracellular signals-regulated Kinase 1 and 2 (ERK1/2), and further noted that, U0126, an ERK1/2 inhibitor, blocks coniferaldehyde-facilitated neurite outgrowth. Moreover, Subchronic administration of CA enhanced learning and memory, and increased neurite length of newborn neurons in the hippocampus. These results suggest that coniferaldehyde induces neurite outgrowth by a process possibly mediated by ERK1/2 signaling and enhances learning and memory. Highlights: Coniferaldehyde facilitated neurite outgrowth of neuro2a cells. Coniferaldehyde did not induced cytotoxicity. Coniferaldehyde activated ERK1/2. ERK1/2 inhibition abolished coniferaldehyde-facilitated neurite outgrowth. Coniferaldehyde enhaced memory and increased neurite outgrowth of newborn neurons in the hippocampus.